Analysis of Reward and Punishment on Employee Performance - Nababan, Pri Rajesti; Partimah, Partimah; Fauzobihi, Fauzobihi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to determine how reward and punishment can affect employeeperformance at Pt. Cakradigdaya Lokaraya. This research with 6 sources in themarkering division is a research written with a qualitative descriptive method thattakes data with observation, interview and observation techniques at Pt. CakradigdayaLokaraya. Cakradigdaya Lokaraya. The results of this study indicate that PtCakradigdaya Lokaraya provides rewards in the form of intenvise every month toemployees who meet project sales targets, year-end vacations for 2 employees andalso promotions, while the punishment given to employees is in the form of late fines,reprimands, sanctions and also the release of positions. While the effect of givingrewards to employees is to motivate employees, provide a sign for an employee if theperformance is superior and also universal in nature so that employees do not feelneglected by the Company. While punishment affects employees by providing adeterrent effect on employees, improving employee discipline, improving performanceresults, evaluating employee performance.